Aplicação da espectroscopia de lente térmica na investigação das propriedades ópticas e térmicas de óleos vegetais comestíveis - Albuquerque, Teresinha Aparecida Soares (2002)
The edible oils are compounds formed by complex structure whose physical and chemical properties are of industrial interest once they can be used to monitor the quality of the commercialized products. Thermal Lens Spectrometry (TLS) is a photothermal technique that has been successfully applied to determine the thermo-optical properties of highly transparent solids, liquids and gases. Recently, the remote nature of the TL technique has been explored to determine the temperature dependence of the thermo-optical properties of transparent materiais. The aim of this work is to apply the thermal lens technique as an alternative method to determine the thermo-optical properties of edible oils. The parameter, θ, which describes the thermal lens signal amplitude, and the thermal diffusity were measured both at room temperature and as a function of the temperature. Complementary measurements as Differential Scanning Calorimetry (DSC), optical absorption coeflicient, refractive index and specific heat were also performed. The studied samples were soya, corn, canola and sunflower oils. The TL experiments were performed with the mode mismatched experimental set up using an argon ion laser at 514.5 nm as the excitation beam and a He-Ne laser at 632.8 nm as the probe beam. The experiments performed at room temperature showed that the sample presented photochemical reaction as a consequence of the illumination with the laser beam. This effect was higher for soya, followed by corn, canola and sunflower oils. It was observed that, by performing the curve fitting with the thermal lens theoretical model we were able to estimate the fraction of the absorbed energy, which was used by the sample to induce photochemical reaction. As a consequence of this procedure the thermo-optical properties of the samples were obtained. The experiments between 18°C and 70°C showed the occurrence of variations in the measured parameters, which were in agreement with the complementary data from specific heat and DSC. This indicates that possible changes in the oil structure, induced by the heating processes, may occur. The results showed that the TL technique were successfully applied to study edible oils and indicates that the use of this method can be extended to study other foods stuffy such as fruit juices.